Inexpensive solar cell using TiO2/coffee composite as photon absorbing material. Issue 1 (May 2020) - Rahman, D Y; Utami, F D; Margaretta, D O; Amalia, N; Sulistyowati, R; Abdullah, M
Abstract: Solar cell using TiO2 /coffee composite as photon absorbing material has been successfully fabricated. A suspension of TiO2 /coffee was dropped on Fluorine Tin Oxide substrate which was previously heated on a hotplate with temperature of 100 °C. The fraction of coffee was varied from 10, 20, 30, 40, and 50 %, compared to the mass of TiO2 . PVA-LiOH electrolyte polymer was functionalized as the hole transport medium. The highest efficiency of 0.76 % was achieved with 40% of coffee fraction. The solar cell is promising to be developed in the future due to the easy method and cheap materials used.